2012
DOI: 10.1111/j.1600-0501.2012.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone physiology in human grafted and non‐grafted extraction sockets – an immunohistochemical study

Abstract: Osteoblastic activity in the provisional matrix was highest after 4 weeks of healing period. The active zone of bone formation is found in the apical region of the extraction socket during the early healing phase, shifting to the coronal region after 12 weeks. A peak of osteoblast activity within the first weeks is followed by a reduction in mature osteoblasts with osteoblasts remaining in an inactive stage. The vascularity changed in likewise fashion to the maturation of osteoblasts within the observation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
2
24
0
3
Order By: Relevance
“…Different authors have suggested that endothelial cells might also play a role on stimulating osteoblasts proliferation and differentiation . An inverse correlation between age and endothelial potential could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have suggested that endothelial cells might also play a role on stimulating osteoblasts proliferation and differentiation . An inverse correlation between age and endothelial potential could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, immunohistochemical and Western blot analyses revealed that RUNX2 expression peaked when monocytic cells were differentiating into fibroblastic cells in the coagulum immediately after extraction and dramatically declined thereafter. RUNX2 is essential in differentiation of mesenchymal stem cells to osteoprogenitor cells during early osteogenesis but not during the maturation stages of bone (4)(5)(6)12). This indicates that RUNX2 functions mainly in the differentiation of mesenchymal stem cells present in the subset of monocytic cells that differentiate into fibroblastic osteoprogenitor cells immediately after tooth extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of ECM proteins to integrins, mechanical loading, fibroblast growth factor-2 (FGF2), parathyroid hormone (PTH), and bone morphogenetic protein (BMP) all regulate the onset of RUNX2 expression (4). RUNX2 is also known as core-binding factor α1 (CBFα1) and β (PEBP2αA) (2,5,6). Information is limited on the contribution of RUNX2 to the healing of wounds created by tooth extraction (2,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences in CD-36, TRAP-1, CD-68 and BMP-4 expression between group 1 (50%AB/50%ABB) and group 2 (20%AB/80%ABB). However, more cellular activity was observed in samples containing more AB Heberer et al (2012) To evaluate osteogenic potential of mesenchymal cells embedded in the provisional matrix of extraction sockets augmented with anorganic bovine bone 6 weeks Cbfa1/Runx2 OSN OC No statistically significant differences in the proportion of positive cells expressed by Cbfa1/Runx2, OSN e OC between grafted and non-grafted sockets Nahles et al (2013) To compare osteogenic potential with the vascularization of the provisional matrix in extraction sockets grafted with anorganic bovine bone 4-12 weeks Cbfa1/Runx2 OC CD-31 CD-31 and OC positive cells significantly higher after 4 weeks; no statistically significant differences in cells expressing Cbfa1/Runx2 between 4 and 12 weeks Galindo-Moreno et al (2014) To evaluate vascular and cellular colonization in anorganic bovine bone graft after maxillary sinus augmentation 6 months CD-44 Osteocyte CD-44 positive cells and neovascularization in ABB particles after 6 months of graft maturation histomorphometrical evaluation, according to the method described by Donath & Breuner (1982). In brief, bone cores were fixed in 10% formalin/0.1 M phosphate buffer saline solution for 10 days, dehydrated in increasing ethanol concentrations and embedded in acrylic resin (Kulzer Technovit 7200 VLC; Bio-Optica, Milano, Italy).…”
Section: Histomorphometrical Analysismentioning
confidence: 99%